Salvianolic acid B ameliorates neuroinflammation and neuronal injury via blocking NLRP3 inflammasome and promoting SIRT1 in experimental subarachnoid hemorrhage - Xia, Dayong; Yuan, Jinlong; Wu, Degang; Dai, Haibin; Zhuang, Zong (Frontiers in Immunology, 2023)
The nucleotide-binding oligomerization domain (NOD)-like receptor family pyrin domain containing 3 (NLRP3) inflammasome-mediated immuno-inflammatory response plays a critical role in exacerbating early brain injury (EBI) after subarachnoid hemorrhage (SAH). Salvianolic acid B (SalB) has previously been shown to suppress neuroinflammatory responses in many disorders. Meanwhile, a previous study has demonstrated that SalB mitigated oxidative damage and neuronal degeneration in a prechiasmatic injection model of SAH. However, the therapeutic potential of SalB on immuno-inflammatory responses after SAH remains unclear. In the present study, we explored the therapeutic effects of SalB on neuroinflammatory responses in an endovascular perforation SAH model. We observed that SalB ameliorated SAH-induced functional deficits. Additionally, SalB significantly mitigated microglial activation, pro-inflammatory cytokines release, and neuronal injury. Mechanistically, SalB inhibited NLRP3 inflammasome activation and increased sirtuin 1 (SIRT1) expression after SAH. Administration of EX527, an inhibitor of SIRT1, abrogated the anti-inflammatory effects of SalB against SAH and further induced NLRP3 inflammasome activation. In contrast, MCC950, a potent and selective NLRP3 inflammasome inhibitor, reversed the detrimental effects of SIRT1 inhibition by EX527 on EBI. These results indicated that SalB effectively repressed neuroinflammatory responses and neuronal damage after SAH. The action of SalB appeared to be mediated by blocking NLRP3 inflammasome and promoting SIRT1 signaling.